Principles of development - Wolpert, Lewis; Wolpert, Lewis; Arias, Alfanso Martinez; Tickle, Cheryll (UK, Oxford, 2015)
Please READ DESCRIPTION Before Buying. The item is Brand New Paperback International/South Asian Edition textbook with 100 % identical Contents as US Edition. Shipped Same Day. Will be dispatched fast. 100% Satisfaction. Great Customer Service, Buy with Confidence, Front Cover May Differ. Ships to PO or APO. May have printed "NOT FOR SALE OUTSIDE of INDIA" or Territorial Disclaimer.
Glossary 599-619p.; Index 621-634p.
Keywords: Cell differentiation and stem cells; Organogenesis; Development of drosophilia